Risk compensation in HIV PrEP adherence among Black men who have sex with men in HPTN 073 study. Issue 5 (4th May 2021) - Whitfield, Darren L.; Beauchamp, Geetha; Fields, Sheldon; Nelson, LaRon; Magnus, Manya; Dācus, Jagadīśa-devaśrī; Paul, Jonathan; Anderson, Peter; Wheeler, Darrell
ABSTRACT: While HIV infections among men who have sex men (MSM) have started to decline in the United States, Black MSM continue to experience disproportionate rates of HIV infection. The purpose of this secondary analysis is to examine risk perception and its influence on PrEP adherence among Black MSM from HPTN 073. Risk perception was measured using the adapted Perceived Vulnerability to HIV Scale. The associations between risk perception and PrEP adherence were tested using generalized estimation equation model for time-variant repeated measures. Risk perception was not significantly associated with PrEP adherence. These findings suggest an there was no risk compensation among PrEP users, and inconsistency in perceived risk for HIV. Future studies should investigate the rationale for long term adherence to PrEP among Black MSM.